Can indicators for sustainable tourism improve tourism planning in the coastal destinations? : Empirical evidence from Catalonia, Istrian Region and Tuscany Region - Brščić, Kristina (Array, 2020)
Due to the continuous increase of the tourism industry, tourism destinations need to be managed under a sustainable framework, with the main aim of minimizing the adverse effects caused by tourism flows. In recent years, several attempts have been made to measure those effects and value the level of sustainability of every destination. A clear example of this is the European Tourism Indicator System (ETIS). In the paper, the results are presented of a project which aimed to test indicators of sustainable tourism in coastal destinations of Catalonia, Istrian Region, and Tuscany Region. The results of 33 collected indicators are available on the online platform of the project INTERREG MED MITOMED+. During the first year, in every category of indicators (economic, social-cultural and environmental) only some indicators were collected, which was expected because different regions apply different methodologies. The collected data is the starting point that shows destinations how the indicator can be obtained and what its purpose is. Furthermore, collected data can help local and regional tourism stakeholders to prevent factors of risk, to take decisions and to improve the implementation of policies for sustainable maritime and coastal tourism development in the Mediterranean area.